PROFIL BERPIKIR KRITIS SISWA SMP DALAM MENYELESAIKAN MASALAH MATEMATIKA DITINJAU DARI KECERDASAN MAJEMUK - Damayanti, Emiliya; Sunardi, Sunardi; Oktavianingtyas, Ervin (Kadikma, 2017)
Abstract. This study describes the of critical thinking in solving mathematical problems basen on multiple intelegences. The instruments used are talent tests, math problem test, and interviews. Research subjects are many six students that is of two students with linguistic intelligence from class VIII F, two students with logical mathematical intelligence from class VIII F, and two students with spatial visual intelligence from class VIII A. Based on the results of analysis and discussion can be concluded that students with linguistic and logical mathematical intelligence meets all critical thinking indicators such as focus, reason, inference, situation, clarifity, and overview. Students with spatial visual intelligence meets critical thinking indicators such as focus, reason, inference, situation, clarifity. Students with spatial visual intelligence does not meet the overview criteria. Keywords: Critical thinking, multiple intelligence, math problems, talent test.